2010
DOI: 10.3390/ijms11062383
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Titanium Dioxide Nanoparticle Aggregate Size on Gene Expression

Abstract: Titanium dioxide (titania) nanoparticle aggregation is an important factor in understanding cytotoxicity. However, the effect of the aggregate size of nanoparticles on cells is unclear. We prepared two sizes of titania aggregate particles and investigated their biological activity by analyzing biomarker expression based on mRNA expression analysis. The aggregate particle sizes of small and large aggregated titania were 166 nm (PDI = 0.291) and 596 nm (PDI = 0.417), respectively. These two size groups were sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(106 citation statements)
references
References 25 publications
5
96
0
2
Order By: Relevance
“…In a previous study Park et al (2008) reported that exposure of BEAS-2B cells to titanium dioxide NPs (5, 10, 20 and 40 μg/ml) induced and increased the expression of the oxidative stress-related genes (including heme oxygenase-1, thioredoxin reductase, glutathione-S-transferase, catalase and hypoxia inducible gene). Okuda-Shimazaki et al (2010) found, using quantitative RT-PCR, that titanium dioxide nanoparticle induce inflammation-related genes, including heat shock protein (HSP) and IL-6 in human acute monocytic leukemia cells (THP-1) and human bronchial epithelial cells (NCI-H292). In the present study, the cytotoxicity and genotoxicity potentials of 3 diverse silicon nanoparticles in HPAEpiC and HPPC cells was evaluated by using MTT, LDH and RT-PCR methods, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study Park et al (2008) reported that exposure of BEAS-2B cells to titanium dioxide NPs (5, 10, 20 and 40 μg/ml) induced and increased the expression of the oxidative stress-related genes (including heme oxygenase-1, thioredoxin reductase, glutathione-S-transferase, catalase and hypoxia inducible gene). Okuda-Shimazaki et al (2010) found, using quantitative RT-PCR, that titanium dioxide nanoparticle induce inflammation-related genes, including heat shock protein (HSP) and IL-6 in human acute monocytic leukemia cells (THP-1) and human bronchial epithelial cells (NCI-H292). In the present study, the cytotoxicity and genotoxicity potentials of 3 diverse silicon nanoparticles in HPAEpiC and HPPC cells was evaluated by using MTT, LDH and RT-PCR methods, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…While sonication may provide a short-term dispersion in solution, aggregates are still present. It is possible that such aggregates may exert a local acute cytotoxicity (Okuda-Shimazaki et al 2010;Gao et al 2010), but…”
Section: Discussionmentioning
confidence: 99%
“…One study has reported specific uptake patterns J U S T A C C E P T E D depending on the cell line between single and aggregated nanoparticles (Albanese et al 2011), whereas another one showed that aggregated nanoparticles lead to a higher cytotoxicity (Okuda-Shimazaki et al 2010). Magnetic nanoparticles such as NWs possess a permanent magnetic moment that makes them more prone to aggregation in solution (Safi et al 2011), with ultrasonic agitation minimizing this effect temporarily.…”
Section: Introductionmentioning
confidence: 99%
“…19 Okuda-Shimazaki et al demonstrated the importance of the aggregation state and showed that larger aggregates of TiO 2 NPs acted more cytotoxically than smaller ones. 20 Phagocytes such as macrophages and monocytes react more strongly to microparticles than to NPs. One study reported higher cell damage for silica microparticles than for NPs, 21 and another study noticed absence of cell damage in THP-1 cells for 30-70 nm silica NPs, while 1000 nm particles acted cytotoxically.…”
Section: Cytotoxicitymentioning
confidence: 99%